2018
DOI: 10.33225/jbse/18.17.215
|View full text |Cite
|
Sign up to set email alerts
|

Design, Development and Evaluation of a Problem-Based With Cooperative Module on Scientific Creativity of Pre-Schoolers

Abstract: The purpose of this research was to design and develop a teaching and learning module using Problem-Based Learning and Cooperative Learning (PBL-CL) and evaluate its effects on scientific creativity of pre-schoolers. The module was developed using the ADDIE instructional design model which included five phases: Analysis, Design, Development, Implementation, and Evaluation. Formative evaluation was conducted to determine the reliability, content validity, pedagogical usability and pre-schoolers’ acceptability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Student creativity will be maximized if students are given responsibility in their learning process (Ayas & Sak, 2018;Suyidno et al, 2017). Other researchers also expressed the same thing, stating that creativity must be supported by a good learning process, a good learning process if students can solve their own problems without any coercion from outside parties (Siew & Chin, 2018). To support a good learning process, one of the models used by teachers is more dominant in student activities (Wibowo, 2021).…”
Section: About Here]mentioning
confidence: 98%
See 1 more Smart Citation
“…Student creativity will be maximized if students are given responsibility in their learning process (Ayas & Sak, 2018;Suyidno et al, 2017). Other researchers also expressed the same thing, stating that creativity must be supported by a good learning process, a good learning process if students can solve their own problems without any coercion from outside parties (Siew & Chin, 2018). To support a good learning process, one of the models used by teachers is more dominant in student activities (Wibowo, 2021).…”
Section: About Here]mentioning
confidence: 98%
“…Scientific creativity is a specific domain that is important for the progress of a nation. Individuals with scientific creativity are more capable of developing original, practical, and unique scientific ideas (Siew & Chin, 2018). Creative scientific ideas are built from extensive theoretical, technical, and experimental construction processes (Hu & Adey, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Early childhood studies on scientific creativity has shown that the Problem-Based Learning and Cooperative Learning (PBLCL) model can encourage children's scientific creativity (Siew et al, 2017;Siew & Chin, 2018). In another study involving children attending second and third grade, it was determined that the STEM program positively affected children's scientific creativity (Ece Genek & Doganca Kucuk, 2020).…”
Section: Scientific Creativity In Early Childhoodmentioning
confidence: 99%
“… When the studies are examined, it is seen that the use of the problem-based cooperative learning model in early childhood science teaching supports the scientific creativity of children (Siew & Chin, 2018). Similarly, studies conducted with older children show that problem-based activities can improve children's scientific creativity (Siew et al 2015).…”
Section: Scientific Creativity In Early Childhoodmentioning
confidence: 99%
See 1 more Smart Citation